Manifolds of absolutely continuous functions with values in an infinite-dimensional manifold and regularity properties of half-Lie groups - Pinaud, Matthieu

Rezension zu: Daniel Drascek, Helmut Groschwitz, Gabriele Wolf (Hg.): Kulturerbe als kulturelle Praxis – Kulturerbe in der Beratungspraxis (Bayrische Schriften zur Volkskunde 12). München 2022 - Leineweber, Jonas (Rheinisch-westfälische Zeitschrift für Volkskunde)

Didaktik der Sozialpädagogik – Entwicklungslinien, Diskurse und Herausforderungen. - Göddertz, Nina (Zeitschrift für Pädagogikunterricht)

Action inhibition in a sport-specific paradigm: examining the limits of action control in basketball - Wickemeyer, Carolin; Güldenpenning, Iris; Weigelt, Matthias (Psychological Research)
Abstract To investigate the point where inappropriate defensive movements can no longer be inhibited and to validate suitable stimulus material for constructing a basketball-specific anticipation-response-inhibition task, two experiments were conducted. In Experiment 1, participants without basketball expertise (N = 25) watched a video of a basketball jump shot and were asked to release the space bar at the point when the ball leaves the player's fingertips (go-trials). In 25% of all trials, the video was stopped prematurely and participants should withhold their finger-lift response (stop-trials). A staircase-tracking algorithm was used to adjust the point-in-time when the jump shot was stopped in a way that participants’ inhibition rate was at 50% (reflecting the so called “point-of-no-return”, PNR). In Experiment 2, the stimulus material was adapted so that stop-trials simulated a pump fake. The PNR in Experiment 1 was located 187 ms and in Experiment 2 177 ms before the point of ball release. Precision performance benefit from practice across blocks and participants delayed their responses after stop-trials in a subsequent go-trial, which reflects strategic post-stop-trial adjustments. Based on the comparable results of previous studies, the given stimulus material is suitable for investigating response inhibition skills in dynamic sport-specific environments.

Émile Durkheim: Father of the Sociology of Education - Lin-Januszewski, Liang-Wen (The Palgrave Handbook of Educational Thinkers)
The establishment of the sociology of education is attributed to Émile Durkheim, one of the founding fathers of sociology. Durkheim’s fervent commitment to the sociological foundations of research methods and the inherent nature of education distinguish the sociological perspective on education from its counterparts in other social sciences, thereby inaugurating the inception of theoretical paradigms within the field of sociology of education. This chapter delineates the motivational forces behind Durkheim’s exploration of education’s multifaceted functions through the lens of social inquiry. It also discusses Durkheim’s significant contributions to the sociology of education, including innovative sociological methods for investigating educational phenomena and his three prominent books: Education and Sociology, Moral Education, and The Evolution of Educational Thought. New insights derived from Durkheim’s conceptualization of functionalism applied to the study of education are also presented. Concluding this chapter is a contemplative reflection on the unfinished intellectual endeavor of interpreting Durkheim’s work through the conflict tradition. This approach has been consistently overlooked, yet it provides valuable insights and unveils profound explanatory mechanisms for sociological analyses of education.

Das Forschungsprojekt im Spiegel praxistheoretischer inklusionsbezogener Unterrichtsforschung - Schröer, Franz; Reis, Oliver; Kruse, Iris; Rohlfing, Katharina (Inklusion verstehen. Szenen aus dem Unterricht in interdisziplinärer Reflexion)

YouTube-Fitness als exemplarisches Phänomen einer Kultur der Digitalität. Medienkompetenzanalytische Perspektiven auf eine körperfokussierte Lifeloggingpraxis. - Burgfeld-Meise, Bianca; Dehmel, Lukas (Jahrbuch Medienpädagogik 21. Mit Medienpädagogik in die Zukunft.)

LFB-Labs-digital: Schülerlabore als Ort der Lehrkräftefortbildung in der digitalen Welt: Ein Bericht zur Konzeption eines Verbundprojektes - Kirchhoff, Tim; Schwedler, Stefanie; Abels, Simone; Acher, Andres; Anselmetti, Dario; Besa, Kris-Stephen; Biehl, Jonathan; Blumberg, Eva; Breiter, Andreas; Brückmann, Maja; Büntemeyer, Doreen; El Tegani, Mahdi; et al. (PFLB – PraxisForschungLehrer*innenBildung)
Schülerlabore haben unter anderem zum Ziel, die Motivation, insbesondere das Interesse – i.S. einer gegenstandsbezogenen Motivation – von Schüler*innen an MINT-Themen und -Arbeitsweisen zu fördern. Darüber hinaus konnten sie sich schneller und produktiver als die formalen Bildungsorte den Herausforderungen der digitalen Transformation stellen. Das Potenzial, Schülerlabore auch als innovative Orte der Lehrkräftefortbildung (LFB) zu nutzen und digitalisierungsbezogene Kompetenzen bei Lehrkräften aufzubauen, wurde bisher nicht ausgeschöpft. Im Verbundprojekt mit insgesamt acht Standorten werden Schülerlabore zu LFB-Labs-digital ausgebaut und die Frage nach Implementierungsvoraussetzungen gelingender Fortbildungen in der digitalen Welt im MINT-Bereich bearbeitet. In diesem Artikel werden die theoretische Fundierung, Ziele und anvisierten Forschungsarbeiten des Verbunds LFB-Labs-digital dargelegt. Zur Unterstützung der mit der forschungsbasierten Qualitätsentwicklung der MINT-bezogenen Aus-, Fort- und Weiterbildung von Lehrkräften betrauten Einrichtungen in den Ländern sollen in Kooperation mit dem Kompetenzzentrum MINT des Bundes die Lernorte „Schülerlabore“ für die digitale LFB erschlossen werden, um vermittelt hierüber die Motivation von Schüler*innen für die MINT-Fächer zu fördern. Die in den Schülerlaboren evaluierten und vom fächerübergreifenden adaptiven Qualitätsmanagement für die LFB wissenschaftlich begleiteten Good-Practice-Beispiele werden zur Grundlage für den „Referenzrahmen LFB-Labs-digital“. Dieser wird – vor dem Hintergrund einer Ergebnistriangulation aus der Begleitforschung sowie den damit parallelisierten Studien zur Evidenzbasierung der Lehrkräftequalifizierung in der digitalen Welt und dem Musterqualitätshandbuch LFB – entwickelt und von einem Implementierungsbeirat mit ausgewiesenen Expert*innen in diesem Bereich auf Transferoptionen hin geprüft. Die digitale Infrastruktur für die LFB-Labs-digital-Veranstaltungsformate wird hierzu prozessbegleitend ausgebaut.

Disentangling Dialect from Social Bias via Multitask Learning to Improve Fairness - Spliethöver, Maximilian; Menon, Sai Nikhil; Wachsmuth, Henning (Findings of the Association for Computational Linguistics ACL 2024)
Dialects introduce syntactic and lexical variations in language that occur in regional or social groups. Most NLP methods are not sensitive to such variations. This may lead to unfair behavior of the methods, conveying negative bias towards dialect speakers. While previous work has studied dialect-related fairness for aspects like hate speech, other aspects of biased language, such as lewdness, remain fully unexplored. To fill this gap, we investigate performance disparities between dialects in the detection of five aspects of biased language and how to mitigate them. To alleviate bias, we present a multitask learning approach that models dialect language as an auxiliary task to incorporate syntactic and lexical variations. In our experiments with African-American English dialect, we provide empirical evidence that complementing common learning approaches with dialect modeling improves their fairness. Furthermore, the results suggest that multitask learning achieves state-of-the-art performance and helps to detect properties of biased language more reliably.

Artificial Intelligence - Naudé, Wim; Gries, Thomas; Dimitri, Nicola
Is Artificial Intelligence a more significant invention than electricity? Will it result in explosive economic growth and unimaginable wealth for all, or will it cause the extinction of all humans? Artificial Intelligence: Economic Perspectives and Models provides a sober analysis of these questions from an economics perspective. It argues that to better understand the impact of AI on economic outcomes, we must fundamentally change the way we think about AI in relation to models of economic growth. It describes the progress that has been made so far and offers two ways in which current modelling can be improved: firstly, to incorporate the nature of AI as providing abilities that complement and/or substitute for labour, and secondly, to consider demand-side constraints. Outlining the decision-theory basis of both AI and economics, this book shows how this, and the incorporation of AI into economic models, can provide useful tools for safe, human-centered AI.

Lernvideos in der Mathematik – Beiträge zur Abschlusstagung des Projektes studiVEMINTvideos der Universität Paderborn und der TH Köln

Death Education im Sachunterricht - eine qualitative Untersuchung zu Vorstellungen von Grundschulkindern - Magdeburg, Lena Maria (Grundschulforschung meets Kindheitsforschung reloaded)

Experimental investigations of uniaxial and biaxial cold stretching within PC‐films and bars using optical measurements - Hamdoun, Ayoub; Mahnken, Rolf (PAMM)
Abstract Polycarbonate (PC) is an amorphous polymer that is an extremely robust material with a high tenacity, and thus suitable for a lightweight construction with glass‐like transparency. Due to these advantageous properties, PC is often used in industry for example in medical devices, automotive headlamps, sporting equipment, electronics, and a variety of other products. PC is often subjected to uniaxial and biaxial loading conditions. Therefore, reliable material models have to take into account the various resulting experimental effects. For those reasons, we investigate PC specimens under uniaxial and biaxial loading by using different stretch rates and loading scenarios. In addition to that, we propose methods for optical measurement of local stretches to obtain the approximated local true stress. In future work, the displacement fields and the resulting reaction forces will be used for parameter identification of constitutive equations.

Uniaxial and biaxial experimental investigation of glassy polymers - Hamdoun, Ayoub; Mahnken, Rolf (Polymer)

Multi-Objective Optimization for Sparse Deep Multi-Task Learning - Hotegni, Sedjro Salomon; Berkemeier, Manuel Bastian; Peitz, Sebastian (2024 International Joint Conference on Neural Networks (IJCNN))
Different conflicting optimization criteria arise naturally in various Deep Learning scenarios. These can address different main tasks (i.e., in the setting of Multi-Task Learning), but also main and secondary tasks such as loss minimization versus sparsity. The usual approach is a simple weighting of the criteria, which formally only works in the convex setting. In this paper, we present a Multi-Objective Optimization algorithm using a modified Weighted Chebyshev scalarization for training Deep Neural Networks (DNNs) with respect to several tasks. By employing this scalarization technique, the algorithm can identify all optimal solutions of the original problem while reducing its complexity to a sequence of single-objective problems. The simplified problems are then solved using an Augmented Lagrangian method, enabling the use of popular optimization techniques such as Adam and Stochastic Gradient Descent, while efficaciously handling constraints. Our work aims to address the (economical and also ecological) sustainability issue of DNN models, with a particular focus on Deep Multi-Task models, which are typically designed with a very large number of weights to perform equally well on multiple tasks. Through experiments conducted on two Machine Learning datasets, we demonstrate the possibility of adaptively sparsifying the model during training without significantly impacting its performance, if we are willing to apply task-specific adaptations to the network weights. Code is available at https://github.com/salomonhotegni/MDMTN.

A large deformation gradient theory for glassy polymers by means of micromorphic regularization - Hamdoun, Ayoub; Mahnken, Rolf (Archive of Applied Mechanics)
Abstract Cold forming of polycarbonate films results in the formation of shear bands in the necking zone. The numerical results obtained from standard viscoplastic material models exhibit mesh size dependency, requiring mathematical regularization. For this purpose, we present in this work a large deformation gradient theory for a viscoplastic isotropic material model published before. We extend our model to a micromorphic model by introducing a new micromorphic variable as an additional degree of freedom along with its first gradient. This variable represents a microequivalent plastic strain. The relation between the macroequivalent plastic strain and the micromorphic variable is accomplished by a micromorphic coupling modulus. This coupling forces proximity between the macro- and microvariables, leading to the targeted regularization effect. The micromorphic model is implemented as a three-dimensional initial boundary value problem in an in-house finite element tool. The analysis is performed for both uniaxial and biaxial specimens. The provided numerical examples show the ability of our model to regularize shear bands within the specimens and address the issue of localization.

The CHiME-8 DASR Challenge for Generalizable and Array Agnostic Distant Automatic Speech Recognition and Diarization - Cornell, Samuele; Park, Taejin; Huang, Steve; Boeddeker, Christoph; Chang, Xuankai; Maciejewski, Matthew; Wiesner, Matthew; Garcia, Paola; Watanabe, Shinji (arXiv:2407.16447)
This paper presents the CHiME-8 DASR challenge which carries on from the previous edition CHiME-7 DASR (C7DASR) and the past CHiME-6 challenge. It focuses on joint multi-channel distant speech recognition (DASR) and diarization with one or more, possibly heterogeneous, devices. The main goal is to spur research towards meeting transcription approaches that can generalize across arbitrary number of speakers, diverse settings (formal vs. informal conversations), meeting duration, wide-variety of acoustic scenarios and different recording configurations. Novelties with respect to C7DASR include: i) the addition of NOTSOFAR-1, an additional office/corporate meeting scenario, ii) a manually corrected Mixer 6 development set, iii) a new track in which we allow the use of large-language models (LLM) iv) a jury award mechanism to encourage participants to explore also more practical and innovative solutions. To lower the entry barrier for participants, we provide a standalone toolkit for downloading and preparing such datasets as well as performing text normalization and scoring their submissions. Furthermore, this year we also provide two baseline systems, one directly inherited from C7DASR and based on ESPnet and another one developed on NeMo and based on NeMo team submission in last year C7DASR. Baseline system results suggest that the addition of the NOTSOFAR-1 scenario significantly increases the task's difficulty due to its high number of speakers and very short duration.

Computer-Based Generation of Learner-Sensitive Feedback to Argumentative Learner Texts - Kilsbach, Sebastian; Michel, Nadine (Proceedings of the Tenth Conference of the International Society for the Study of Argumentation)
What is learner-sensitive feedback to argumentative learner texts when it is to be issued computer- based? Learning stages are difficult to quantify. The paper provides insight into the history of research since the 1980s and a preview of what this automated feedback might look like. These questions are embedded in a research project at the Universities of Paderborn and Hannover, Germany, from which a software (project name ArgSchool) emerges that will provide such feedback.
Keywords: AI; argumentation mining; discourse history; (automated; learner-sensitive) feedback

Überlegtes und überlegenes Reiten oder Beobachtungen des Affekteinsatzes: Montaigne ‚Des coches' (1588) - Steigerwald, Jörn (Einsatz der Affekte. Zum Schrifttum der europäischen Expansion)

Johann Elias Schlegels Revision der Tyrannentragödie: Die ‚Lucretia' - Steigerwald, Jörn (Johann Elias Schlegel und das Theater. Zwischen Revision und Reform)